A pilot course for training of trainers in agricultural information techniques meeting was held in 1992 - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1996)
pilot course was held from 17 July - 11 August, 1995 in Dakar, Senegal